1998
DOI: 10.1128/jvi.72.11.9061-9068.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Bipartite Membrane-Binding Signal in the Human Immunodeficiency Virus Type 1 Matrix Protein Is Required for the Proteolytic Processing of Gag Precursors in a Cell Type-Dependent Manner

Abstract: It is unclear whether proteolytic processing of the human immunodeficiency virus type 1 (HIV-1) Gag protein is dependent on virus assembly at the plasma membrane. Mutations that prevent myristylation of HIV-1 Gag proteins have been shown to block virus assembly and release from the plasma membrane of COS cells but do not prevent processing of Gag proteins. In contrast, in HeLa cells similar mutations abolished processing of Gag proteins as well as virus production. We have now addressed this issue with CD4+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Mutations which block or impair HIV-1 Gag myristylation have been reported to disrupt virus assembly and reduce the efficiency of Gag processing (4,16,19,27,34). We previously demonstrated that the 6VR mutation did not impair Gag myristylation (33).…”
Section: Mutations Near the N Terminus Of Ma Impair Virus Assembly Anmentioning
confidence: 86%
“…Mutations which block or impair HIV-1 Gag myristylation have been reported to disrupt virus assembly and reduce the efficiency of Gag processing (4,16,19,27,34). We previously demonstrated that the 6VR mutation did not impair Gag myristylation (33).…”
Section: Mutations Near the N Terminus Of Ma Impair Virus Assembly Anmentioning
confidence: 86%
“…Immunoblotting and p24 assay. Three days after transfection, cell lysates were prepared as previously described (14). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was carried out by using standard methods.…”
Section: Construction Of Hiv-1 Gag Expression Vectorsmentioning
confidence: 99%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was carried out by using standard methods. Proteins were transferred to nitrocellulose (Schleicher & Schuell) by washing the gel and nitrocellulose in transfer buffer (50 mM NaCl, 1.8 mM EDTA, 10 mM Tris, pH 7.0) and making a sandwich of nitrocellulose sheets with the gel in the middle, wrapping with plastic wrap, and incubating overnight between two glass plates with a 2-kg weight on top, at 4°C (2a, [14][15][16]35). The blots were stained with HIV-1-positive human serum in a PBS solution with 3% nonfat dried milk.…”
Section: Construction Of Hiv-1 Gag Expression Vectorsmentioning
confidence: 99%
“…The presence of antibodies against several linear sequences showed the immunogenicity of both CP and FP recombinant vectors. The presence of antibodies against the p55 gag precursor may be ascribed to the use of HIV‐infected cells for challenge: while the main core antigen in cell‐free virus is p24, in infected cells the main core antigen is p55 [27]. Recognition by rabbit CTLs of xenogeneic human E‐line cells would cause their lysis and exposure of the intracellular p55 gag precursor, which would in turn be recognized and presented by antigen‐presenting cells in association with MHC class II molecules.…”
Section: Discussionmentioning
confidence: 99%